Support for total hip replacement surgery: Structures modeling, Gait Data Analysis and Report system - Gianluca Mario Izzo (PAGEPress Publications, 2012)
For the treatment of advanced damages of hip joints, Total Hip Arthroplasty is well proven. Due to the different mechanical properties of the prosthesis material and the bone tissue, a partial unloading of the periprosthetic bone occurs. The bone cement causes reduction in bone density as a result of removal of normal stress from the bone, leading to weakening of the bone in that area and the fracture risk increases. Bone loss is identified as one of the main reasons for loosening of the stem. Otherwise, thanks to the press-fit of the non-cemented stem achieved by surgery, the bone layers immediately adjacent to the stem are preloaded, thus encouraged growing, and the bone getting stronger. The non-cemented stem would be the better choice for every patient, but the question remains if the femur can handle the press- fitting surgery. This studies aim to develop a monitoring techniques based on Gait analysis and bone density changes to assess patient recovery after Total Hip Arthroplasty. Furthermore, to validate computational processes based on 3D modeling and Finite Element Methods for optimizing decision making in the operation process and selecting the suited surgical procedure. A vision could be minimizing risk of periprosthetic fracture during and after surgery. Patients: The sample presents 11 patients receiving cemented implant and 13 for the uncemented. Patients are grouped by type of implant. Three checkpoints were considered: before, after operation and one year later. CT scans, gaitrite and kinepro measurements have been realized. Main outcome measures: Fracture risk probability is higher in bone with low bone mineral density; therefore bones are more fragile in elderly people. BMD is indeed one parameter considered among all the observations. Periprosthetic fracture of the femur is a rare but complex complication of THA, and requires demanding surgery. As such, they result in considerable morbidity and dysfunction. Thus, tests of force reaction have been accomplished to support surgeons during the prosthesis fitting. Identification of risk factors for fracture will improve preoperative counseling and aid primary prevention. To assess eventual improvements or find out trends respecting the implant used, gait data have been collected and compared with muscles mass modeling.